A point of view - James, Clive (Picador, 2011)
The BBC Radio 4 series, A Point of View, has been on the air since 2007. Over the years, it's had a variety of presenters - including the national treasure that is Clive James - talking for ten minutes about anything and everything that has captured their imagination, piqued their interest, raised their blood pressure or just downright incensed them that week. Of all the presenters, Clive James was a clear favourite, and now, for the first time, his original pieces - sixty in total - and all new postscripts are collected together in one volume. Read along with Clive as he reflects on everything from wheelie bins to plastic surgery, Elizabeth Hurley to the Olympics, 24 to Damien Hirst, Harry Potter to giving up smoking, car parks to Chinese elections, Britain's Got Talent to the expenses scandal - and plenty more besides. Essentially a chronicle of life in twenty-first century Britain, Clive James A Point of View is informed and informative, thoughtful and thought-provoking - but above all, entertaining. In fact, in short, it's a damn good read.